A retrospective study of 100 cases of Eclampsia: perinatal outcomes - Kannar, Avani; Patel, Manthan; Prajapati, Shetal; Chavda, Dolly (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Eclampsia is associated with devastating maternal and foetal complications. Eclampsia is a major cause of maternal morbidity and mortality in developing countries. Evaluation of factors contributing to occurrence of eclampsia and death of eclamptic mother is of paramount importance. The aim of the study was to determine the perinatal mortality rate in eclamptic women. To assess the perinatal outcome with respect to time between first convulsion and delivery, time of treatment and delivery .To assess the perinatal outcome and mode of delivery. In this study we have tried to know the relationship between maternal blood group and eclampsia. Methods: A retrospective study of 100 cases of eclampsia was done in P.D.U. Medical College, Rajkot. Pregnant woman diagnosed as eclampsia during this period were included. The events and outcome of mother and fetus were recorded and analyzed. Results: Around 60% of patients were primipara and 70% patients were from rural area. On evaluation of background characteristics, 65 patients were not booked, 48% patients were hypertensive and 40% were normotensive. Out of 14 maternal deaths, five had cerebral haemorrhage, 3 had pulmonary edema, 3 had renal failure and 2 developed PPH. Conclusions: Majority of the patients were unbooked and young and primigravida. Fifteen percent of eclamptic women required cesarean delivery. Most common cause for neonatal death was prematurity and its attendant complications.